2022
DOI: 10.1186/s12905-022-01702-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and correlates of cervical cancer screening among women attending a community-based multi-disease health campaign in Kenya

Abstract: Introduction Despite the increased risk of cervical cancer among HIV-positive women, many HIV-care programs do not offer integrated cervical cancer screening. Incorporating self-collected Human Papillomavirus (HPV) testing into HIV programs is a potential strategy to identify women at higher risk for cervical cancer while leveraging the staffing, infrastructure and referral systems for existing services. Community-based HIV and HPV testing has been effective and efficient when offered in single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The current study reported low cervical cancer screening rates among the study participants in both arms. Similar low screening rates were reported by a study among women in Kenya where only 35.6% of the eligible women were screened [ 13 ]. Among Ghanaian women, only 24.6% of those eligible were screened despite the close proximity to facilities offering free cervical cancer screening services [ 14 ].…”
Section: Discussionsupporting
confidence: 84%
“…The current study reported low cervical cancer screening rates among the study participants in both arms. Similar low screening rates were reported by a study among women in Kenya where only 35.6% of the eligible women were screened [ 13 ]. Among Ghanaian women, only 24.6% of those eligible were screened despite the close proximity to facilities offering free cervical cancer screening services [ 14 ].…”
Section: Discussionsupporting
confidence: 84%
“…Modeling studies demonstrate that achieving the 90/70/90 targets will avert 74 million new cases of cervical cancer and 62 million deaths in LMICs. 44 Our findings, along with other studies looking at CCS coverage in Kenya, 45 reveal a great need to scale up CCS coverage in HIV programs caring for women at the highest risk of cervical cancer to attain the WHO elimination targets and save millions of lives. As a result of inadequate secondary prevention for WLWHIV, few of whom were vaccinated against HPV, cervical cancer is a leading cause of cancer death among WLWHIV in LMICs.…”
Section: Discussionmentioning
confidence: 54%
“…This is due to uncertainties surrounding self-collected HPV testing, concerns about self-efficacy in self-sampling [ 32 ], and results delivery [ 29 ] reported elsewhere. Additionally, low uptake of self-collected HPV testing was registered in Kenya among 25-34-year-old women at multi-disease community health fairs [ 38 ], highlighting the importance of tailoring HPV-based self-collection strategies to address the specific needs of women at different age groups. Beneficiary-collected samples being less accurate than clinician-collected ones due to potential user error and lack of familiarity with the procedure have been reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%